Sympathetic Crashing Acute Pulmonary Edema in a Postoperative Case of Pituitary Macroadenoma - Jain, Varun; Singh, Swati; Kaur, Ruchinder; Gupta, Rahul (Journal of Neuroanaesthesiology and Critical Care, 2025)
We present a case of 58-year-old male operated for pituitary macroadenoma. On the 7th postoperative day, the patient developed sudden-onset breathlessness and desaturation needing ventilatory support. His cardiac function, which was normal preoperatively, deteriorated (ejection fraction 20%) but cardiac enzyme levels were normal. Chest X-ray was suggestive of pulmonary edema. His condition stabilized with the use of noninvasive mechanical ventilation, high-dose nitroglycerine (NTG) infusion, and furosemide over the next 12 hours. Cardiac functions improved to baseline after about a week.Sympathetic crashing acute pulmonary edema is life-threatening entity and needs urgent intervention. It should be differentiated from cardiogenic or neurogenic pulmonary edema because treatment involves rapid lowering of blood pressure with the use of high-dose systemic vasodilators like NTG. On initial assessment, clinical condition may be confused with acute decompensated heart failure due to myocardial infarction.
Keywords: nitroglycerine; pituitary macroadenoma; sympathetic crashing acute pulmonary edema